Efficient and Affordable Cancer Screening through Analysis of Glyceraldehyde-3-Phosphate Dehydrogenase (GAPDH) Gene Expression in Circulating Cell-Free DNA and RNA - Ara, H.; Al-Din, S. M. S.; Tarek, S. A.; Biswas, M. K.; E. Hoque; Faruque, S. B.; Haque, Y.; Sharafuddin, S. M. (Journal of Scientific Research, 2025)
This research aims to address challenges by proposing a swift and cost-efficient methodology for cancer detection. The study involved 80 (eighty) participants, comprising 40 (forty) diagnosed with cancer and an equivalent number without any known cancer diagnosis, all of whom provided informed consent. The real-time quantitative polymerase chain reaction (RT-qPCR) targeting the human-specific glyceraldehyde 3-phosphate dehydrogenase (GAPDH) gene was employed as a novel method for reliable and precise quantification of circulating cell-free DNA (ccfDNA) in human blood plasma. Additionally, three other housekeeping genes, namely beta-actin (ACTB), ubiquitin C (UBC), and hypoxanthine-guanine phosphoryl transferase (HPRT1), were employed as reference genes for the relative quantification of GAPDH in circulating cell-free mRNA (ccfmRNA). In addition to assessing GAPDH gene expression in ccfDNA, the findings were validated by examining the expression of these three reference genes in circulating cell-free mRNA (ccfmRNA). The results demonstrated a significantly elevated expression (p< 0.001) of the GAPDH gene in both ccfDNA and ccfmRNA within plasma samples of cancer patients compared to those individuals without cancer diagnosis. This study underscores the reliability and effectiveness of assessing GAPDH gene expression in ccfDNA using RT-qPCR, establishing it as a promising tool for rapid cancer diagnosis.